Active and Stable Layered Alkali Iridates Efficiently Catalyze Oxygen Electroevolution in Low-Ir Proton-Exchange Membrane (PEM) Water Electrolyzers - Kang, Jiaqi; Möhle, Sebastian; Wang, Xingli; Kovács, Miklós Márton; Drnec, Jakub; Nasralla, Kerolus N.N.; Buchheister, Paul W.; Schmidt, Johannes; Dworschak, Dominik; Strasser, Peter (Journal of the American Chemical Society, 2025)
Developing catalysts with improved activity and stability compared to rutile IrO2 or amorphous IrOx remains a technical priority for advancing the oxygen evolution reaction (OER) in proton-exchange membrane water electrolyzers (PEMWEs). Here, we report structure-OER activity-stability relationships across a family of alkali cation-intercalated iridates, uncovering a structural evolution from hollandite to layered-type structures, characterized by the ratio of edge-sharing to corner-sharing connections of [IrO6] octahedral motifs. In particular, Li-IrOx and Cs-IrOx demonstrate excellent PEMWE performance over a wide current range, pushing Ir demand to new lows. Both achieve a power-specific Ir demand of 0.06 gIr kW-1. However, Cs-IrOx shows a greater potential for long-term stability, indicating that iridates with a higher proportion of edge-sharing motif connections possess enhanced structural robustness. This work offers new insights into balancing catalytic activity and stability through atomic-scale motif connectivity tuning and presents a viable alternative to state-of-the-art rutile or amorphous iridium oxides.
CRIS-Team Scopus Importer:2025-12-26